(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To learn religion as far as social change as Vivekananda puts forward is to take in the soul inborn in it. Also, to learn it is to be earnestly engaged with it, to such an extent that it must enter profound into the innermost being. Religion, in this manner, is a nonstop askance and enquiry into the heartland of humanity. The heartland is certainly an unpredictable one welcoming a test - a test to find and rediscover oneself as far as virtue and steadiness. Vivekananda, accordingly, affirms the significance of immaculateness of soul, which enables religion to be sought after regarding humanity. He asserts that immaculateness is the essential for religion to create in the human spirit. He additionally recommends that the virtue of essence ought to be combined with the sharp and unquenchable want to pick up learning. One ought to be wholeheartedly committed to this journey for information and not be disheartened by limitations of time as this mission may include many lifetimes.